"Pay for delay" - Straus, Joseph (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2016)
The relationship between antitrust law and intellectual property rights, as exclusive rights, i.e. legal monopolies, has always been characterized by a mutual distrust of protagonists of either discipline. Only more recently the understanding started to prevail that intellectual property and antitrust laws work in tandem to bring new and better technologies, products and services to consumers at lower prices. The judicial treatment of the so-called "pay for delay" patent settlement agreements by courts and antitrust authorities, however, demonstrates how complicate and problem-burdened the application of antitrust law on legal transactions at the crossroads of antitrust law and patent law is and how difficult it is to achieve well balanced solutions satisfying the goals of both disciplines. In this contribution the legal situation under the US law, as applied by the US Supreme Court in the Actavis case, and under the EU law, as applied by the EU Commission in the Servier case is examined and the differences elaborated by taking into account the relevant facts of each case. The approach of the EU Commission is, eventually, critically reviewed in the light of the recent interpretation of Article 101 of the Treaty on the Functioning of the European Union by the Court of Justice of the European Union in the Groupement des Cartes Bancaires case.
Keywords: intelektualna lastnina; patenti; karteli; pravna ureditev